Analisis privasi data pengguna contact tracing application pengendalian COVID-19 di Indonesia berdasarkan PERPRES RI No. 95 tahun 2018 tentang sistem pemerintahan berbasis elektronik - Suwandi, Syifa Ilma Nabila; Seloatmodjo, Xavier Wahyuadi; Situmorang, Alexandra; Rakhmawati, Nur Aini (Universitas Pesantren Tinggi Darul 'Ulum (Unipdu) Jombang, 2021)
The presence of user contact applications in the community as a means of preventing and overcoming the spread of COVID-19 can pose another risk to the potential dangers of protecting data privacy from contact tracing. This research examines more deeply related to user privacy policies through 3 (three) samples of android-based user contact applications that are used as a means of preventing, overcoming and controlling the spread of the COVID-19 virus in today's society and by reviewing the rules contained in the Presidential Regulation of the Republic. Indonesian No. 95 of 2018 concerning Electronic-Based Government Systems (SPBE). The study in this study was prepared using the method of literature study, observation and qualitative analysis. A comparison was made regarding the data privacy of the three samples, which was then evaluated and matched with the form of the privacy policy according to Presidential Regulation No. 95 of 2018 concerning Electronic-Based Government Systems (SPBE) and according to the ideal form of data privacy policy based on several experts. Comparative data is obtained through related applications and other electronic media which are then discussed together to conclude and evaluate the data privacy policies of the three sample applications. Based on this research, it can be concluded that privacy intervention to deal with damage and save lives is legal as long as its use is in accordance with regulations in the health, disaster, telecommunications, informatics and other related fields; in this case listed in the Presidential Decree No. 95 of 2018 concerning Electronic-Based Government Systems (SPBE) and there needs to be an increase in efforts to maintain the security and confidentiality of user data privacy through continuous system and data maintenance, encryption of data privacy storage in the manager's data warehouse and added with other data privacy policies can guarantee the security and confidentiality of the privacy of user data.